A DEBATE BETWEEN A THEIST AND A SANTA CLAUSIST (ACT I). Issue 40 (9th April 2015) - Tallman, Ruth; Johnson, David Kyle
Abstract : Many claim that belief in God is like belief in Santa Claus – it's an irrational belief that people justify with irrational arguments because they cherish it and because it comforts them. In this dialogue, true believers 'have it out' regarding whether either of their beliefs – belief in God, or belief in Santa – is rational, and a direct parallel between the reasoning of the two sides is demonstrated. Many important arguments regarding theistic belief are discussed in some form. The article is intended for use in an introduction to philosophy, or an introductory philosophy of religion course, as a humorous way to foster discussion and expose students to criticisms of theistic arguments, and to consider the possibility that theistic belief is no better than belief in the existence of Santa Claus. Act One.